Ответы и объяснения

2013-05-19T18:28:33+00:00

а-                                                 в-                         г-

-(4-х)-4(х-5)=5(1-х)                   /х-1/=3                /3х/-1=11

-4+х-4х+20=5-5х                       х-1=3                   3х-1=11

х-4х+5х=5-20+4                         х=3+1                   3х=11+1

2х=11                                           х=4                         3х=12

х=11:2                                                                          х=12:3

х=5,5                                                                             х=4